Digital governance for citizen engagement: an analysis of citizen-centered applications in India - Bagul, Anu; Chaudhary, Rouchi; Mahajan, Siddharth; Shandilya, Shivendra (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The Government of India has launched several mobile applications such as UMANG, mAadhaar, Digilocker, and CPGRAMS to facilitate citizen engagement and improve public service delivery. These platforms serve as a testament to the ongoing digital transformation in governance, aimed at making services more accessible, transparent, and efficient. The study evaluates the impact of digital applications like Unified Mobile Application for New-age Governance (UMANG), mAadhaar, Digilocker and Centralised Public Grievance Redress and Monitoring System (CPGRAMS) on citizen engagement and governance effectiveness. A mixed-methods approach was adopted, integrating qualitative and quantitative insights from 400 respondents across varied demographics were surveyed and 20 qualitative in-depth interviews conducted on experts across India. Findings highlight significant disparities in accessibility and usability of these tools, calling for integrated policy interventions and advanced technology adoption. The paper also discusses challenges such as digital divide and proposes actionable recommendations to optimize citizen-centric services.